2022
DOI: 10.1111/aec.13166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topsoil transposition on the taxonomic and functional diversity of macrofauna of highly degraded soil

Abstract: Topsoil transposition has been identified as an environmental restoration technique capable of accelerating regeneration in degraded areas. In addition to the seed bank, topsoil contains invertebrates and microorganisms essential in ecological succession. This study evaluated the temporal variation in the macrofauna community structure in an experiment with topsoil transposition. We hypothesized that the morphospecies richness, functional groups and macrofauna biomass would be higher in the plots with topsoil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
1
0
0
Order By: Relevance
“…Mites from families such as Bdellidae and Trombidiidae also contributed to this pattern (Appendix S1: Table S6). Although we did not calculate biomass, our results are similar to Parreira et al (2022) who found invertebrate predator biomass increased after inoculating restoration sites with remnant topsoil. This suggests that predaceous species may be most likely to establish during whole‐of‐community rewilding, regardless of the inoculation source (e.g., soil/litter/wetland sediment etc.…”
Section: Discussionsupporting
confidence: 89%
“…Mites from families such as Bdellidae and Trombidiidae also contributed to this pattern (Appendix S1: Table S6). Although we did not calculate biomass, our results are similar to Parreira et al (2022) who found invertebrate predator biomass increased after inoculating restoration sites with remnant topsoil. This suggests that predaceous species may be most likely to establish during whole‐of‐community rewilding, regardless of the inoculation source (e.g., soil/litter/wetland sediment etc.…”
Section: Discussionsupporting
confidence: 89%